1996
DOI: 10.1177/108835769601100305
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study Evaluation of a Transfer-of-Stimulus Control Toilet Training Procedure for a Child with Pervasive Developmental Disorder

Abstract: This case study evaluated a transfer-of-stimulus control prompting procedure to promote in-toiiet urinating by a 7-year-old girl with pervasive developmental disorder within a public school program. Before training, the girl displayed frequent urinary incontinence and never urinated in the toilet The prompting procedure consisted of her wearing a diaper, a stimulus associated with urinating, while sitting on the toilet. This arrangement was instituted for 2 weeks with moderate success, whereafter the girl inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Such mounting evidence indicates that intensive behavioral toileting procedures are effective with children with pervasive developmental disorders and that they can be implemented in home and school settings by parents and school staff members, in addition to behavioral specialists. Furthermore, recent studies have investigated transfer-of-stimulus-control procedures (Luiselli, 1996), priming (Bainbridge & Myles, 1999), and socially maintained incontinence (Ricciardi & Luiselli, 2003), all with children with pervasive developmental disorders. Taken together, the aforementioned studies indicate renewed attention to the treatment of incontinence in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Such mounting evidence indicates that intensive behavioral toileting procedures are effective with children with pervasive developmental disorders and that they can be implemented in home and school settings by parents and school staff members, in addition to behavioral specialists. Furthermore, recent studies have investigated transfer-of-stimulus-control procedures (Luiselli, 1996), priming (Bainbridge & Myles, 1999), and socially maintained incontinence (Ricciardi & Luiselli, 2003), all with children with pervasive developmental disorders. Taken together, the aforementioned studies indicate renewed attention to the treatment of incontinence in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Using surveys, researchers have found that the majority of parents of children with autism report toileting and urination problems (Whiteley, 2004; Williams, Oliver, Allard, & Sears, 2003), and these concerns have stimulated research specifically with this population. For example, several investigations (Cicero & Pfadt, 2002; Luiselli, 1996, 1997; Post & Kirkpatrick, 2004) have evaluated versions of the Azrin and Foxx (1971) treatment package with children with autism and other pervasive developmental disorders. In the most recent empirical investigation of a version of this treatment package, LeBlanc, Crossett, Bennett, Detweiler, and Carr (2005) reported outcomes for three children with autism who received services at an outpatient clinic.…”
mentioning
confidence: 99%
“…Three studies implemented this diaper fading procedure when children did not urinate in the toilet. Luiselli ( 1996b ) initiated diaper fading with a participant who only urinated in disposable diapers, despite repeated caregiver attempts to prompt continent urination. After the participant was reliably urinating on the toilet while wearing a diaper, she began to sit on the toilet independently before the altered diaper could be applied during training sessions.…”
Section: Resultsmentioning
confidence: 99%